Benefits of future satellite gravimetry missions for characterizing extreme wet events in terrestrial water storage - Klara Middendorf; Laura Jensen; Marius Schlaak; Julian Haas; Henryk Dobslaw; Roland Pail; Andreas Güntner; Annette Eicker (Advances in Space Research, 2026)

Using Satellite-Based Terrestrial Water Storage Data: A Review - Vincent Humphrey; Matthew Rodell; Annette Eicker (Surveys in Geophysics, 2023)
Land water storage plays a key role for the Earth’s climate, natural ecosystems, and human activities. Since the launch of the first Gravity Recovery and Climate Experiment (GRACE) mission in 2002, spaceborne observations of changes in terrestrial water storage (TWS) have provided a unique, global perspective on natural and human-induced changes in freshwater resources. Even though they have become much used within the broader Earth system science community, space-based TWS datasets still incorporate important and case-specific limitations which may not always be clear to users not familiar with the underlying processing algorithms. Here, we provide an accessible and illustrated overview of the measurement concept, of the main available data products, and of some frequently encountered technical terms and concepts. We summarize concrete recommendations on how to use TWS data in combination with other hydrological or climatological datasets, and guidance on how to avoid possible pitfalls. Finally, we provide an overview of some of the main applications of GRACE TWS data in the fields of hydrology and climate science. This review is written with the intention of supporting future research and facilitating the use of satellite-based terrestrial water storage datasets in interdisciplinary contexts.

Monthly and sub-monthly hydrological variability: in-orbit validation by GRACE level 1B observations - Annette Eicker; Anne Springer (Journal of Geodesy, 2016)

Science and User Needs for Observing Global Mass Transport to Understand Global Change and to Benefit Society - Roland Pail; Rory Bingham; Carla Braitenberg; Henryk Dobslaw; Annette Eicker; Andreas Güntner; Martin Horwath; Eric Ivins; Laurent Longuevergne; Isabelle Panet; Bert Wouters (Surveys in Geophysics, 2015)

Calibration/Data Assimilation Approach for Integrating GRACE Data into the WaterGAP Global Hydrology Model (WGHM) Using an Ensemble Kalman Filter: First Results - Annette Eicker; Maike Schumacher; Jürgen Kusche; Petra Döll; Hannes Müller Schmied (Surveys in Geophysics, 2014)

Seasonal Water Storage Variations as Impacted by Water Abstractions: Comparing the Output of a Global Hydrological Model with GRACE and GPS Observations - Petra Döll; Mathias Fritsche; Annette Eicker; Hannes Müller Schmied (Surveys in Geophysics, 2014)

Multivariate Prediction of Total Water Storage Changes Over West Africa from Multi-Satellite Data - Ehsan Forootan; Jürgen Kusche; Ina Loth; Wolf-Dieter Schuh; Annette Eicker; Joseph Awange; Laurent Longuevergne; Bernd Diekkrüger; Michael Schmidt; C. K. Shum (Surveys in Geophysics, 2014)

The ITG-Goce02 gravity field model from GOCE orbit and gradiometer data based on the short arc approach - Judith Schall; Annette Eicker; Jürgen Kusche (Journal of Geodesy, 2014)

Regional gravity modeling in terms of spherical base functions - Michael Schmidt; Martin Fengler; Torsten Mayer-Gürr; Annette Eicker; Jürgen Kusche; Laura Sánchez; Shin-Chan Han (Journal of Geodesy, 2007)